2009
DOI: 10.2478/s11756-009-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of common carp (Cyprinus carpio) populations from Greece using mitochondrial DNA sequences

Abstract: Wild common carp from two lakes and two rivers in Greece were genetically characterized with sequencing analysis of two mitochondrial DNA segments: cytochrome b (1119 bp) and D-loop (646 bp). A total of 9 variable singleton sites and 7 unique haplotypes were detected. A common haplotype was found in three out of the four populations examined, which seems to be the ancestral one and represents the European origin of common carp from Greece. This haplotype could be also justified by the introductions reported wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
8
1
Order By: Relevance
“…Similar values were reported for both wild and domesticated common carp from Germany, Spain and some Balkan countries (H o = 0.640-0.840, Bartfai et al 2003;Kohlmann et al 2005), as well as for Russian breeders (Kohlmann et al 2005;Memis and Kohlmann 2006) and in some cases lower heterozygosity levels (Zhou et al 2004;Li et al 2007;Thai et al 2007) compared with those in Europe. The present results, however, are not in agreement with the data obtained by mitochondrial analysis on four of the studied populations (Imsiridou et al 2009). Those authors found no genetic variation for the common carp populations from Evros, Aliakmon and Doirani while maximum haplotypic diversity was reported for L. Volvi.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar values were reported for both wild and domesticated common carp from Germany, Spain and some Balkan countries (H o = 0.640-0.840, Bartfai et al 2003;Kohlmann et al 2005), as well as for Russian breeders (Kohlmann et al 2005;Memis and Kohlmann 2006) and in some cases lower heterozygosity levels (Zhou et al 2004;Li et al 2007;Thai et al 2007) compared with those in Europe. The present results, however, are not in agreement with the data obtained by mitochondrial analysis on four of the studied populations (Imsiridou et al 2009). Those authors found no genetic variation for the common carp populations from Evros, Aliakmon and Doirani while maximum haplotypic diversity was reported for L. Volvi.…”
Section: Discussioncontrasting
confidence: 99%
“…There is no available study focusing on the genetic stability and Ne over time for this species. In Greece, common carp has been studied using mitochondrial DNA (Imsiridou et al 2009;Tsipas et al 2009). However, microsatellite DNA markers have not been used before to study Greek wild common carp populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the very high level of gene flow resulting from massive hybridisation of the (putative) wild form with historical stockings of domesticated forms (Economidis et al 2000), it is likely that true wild populations no longer exist in the area. This has been supported genetically by Imsiridou et al (2009), who were able to identify a common haplotype in three out of four populations from Macedonia and Thrace, thereby pointing to their ancestral, though not necessarily wild, status.…”
Section: Originmentioning
confidence: 79%
“…Although native to Macedonia and Thrace (Imsiridou et al 2009), several introductions initially occurred from Italy to central and western Greece in the late 1930s, followed by translocations since the 1950s as L. VILIZZI 98 well as later introductions of mostly domesticated forms from Israel and Hungary in the 1980s (Economidis et al 2000;Leonardos et al 2008;Perdikaris et al 2010). Carp was dominant in catches from Lake Tavropos , and a survey of 18 protected lakes and reservoirs in Greece indicated its presence in all ecosystems (Drakou et al 2009).…”
Section: Greecementioning
confidence: 99%
“…The wild ancestor of domesticated carp probably lived in the Caspian and Aral Sea basins, from where it was dispersed both to Western Europe and to East Asia. The current natural distribution of common carp ranges from Europe throughout the continent of Eurasia to China, Japan and South East Asia (Balon, 1995(Balon, , 2006Imsiridou et al, 2009;Chistiakov and Voronova, 2009). C. carpio is omnivore species that entered the Çamlıgöze Dam Lake with introducing studies.…”
Section: Discussionmentioning
confidence: 99%